2021
DOI: 10.1101/2021.03.09.434438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MEYE: Web-app for translational and real-time pupillometry

Abstract: Pupil dynamics alterations have been found in patients affected by a variety of neuropsychiatric conditions, including autism. Studies in mouse models have used pupillometry for phenotypic assessment and as a proxy for arousal. Both in mice and humans, pupillometry is non-invasive and allows for longitudinal experiments supporting temporal specificity, however its measure requires dedicated setups. Here, we introduce a Convolutional Neural Network that performs on-line pupillometry in both mice and humans in a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The ideal solution would be to measure a full set of pupillometric features from the RGB cameras embedded on the robotic platform. Recent findings suggest that this approach could be feasible [43][44][45][46]74]; hence, we look forward to removing this limitation, making the system completely non-intrusive. Other than due to cognitive load changes, pupil dilation tends to be affected by other factors like excitement, stress, and environmental light conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal solution would be to measure a full set of pupillometric features from the RGB cameras embedded on the robotic platform. Recent findings suggest that this approach could be feasible [43][44][45][46]74]; hence, we look forward to removing this limitation, making the system completely non-intrusive. Other than due to cognitive load changes, pupil dilation tends to be affected by other factors like excitement, stress, and environmental light conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Both, mobile head mounted [39,40], and remote eye tracker [41,42] devices have been used as minimally invasive methods to measure pupillometric features, more appropriate for real-world scenarios. Recent research showed the possibility to measure TEPRs from RGB cameras, suitable for robotic platforms, making pupillometry a promising candidate to detect lies in real-life human-robot interactions [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…To validate such multimodal system on our setup, aiming to port it to a real-world scenario, it would be mandatory to overcome the limitation posed by the Tobii Pro Glasses 2 eyetracker since it partially occludes actors' faces, limiting the usage of visual features. Recent findings [29] suggest it will be soon possible to measure pupillometric features with common RGB cameras like the ones embedded on the iCub robotic platform. Finally, it would be necessary to push the research field to more ecological and real-life scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…During fear conditioning mice were head-xed and free to run on a circular treadmill. An infrared webcam was used to record the pupil and the MEYE Deep Learning tool was employed to perform pupillometry [23] (Fig. 2A).…”
Section: Lack Of Crtl-1 Accelerates Extinction Of Fear Memories In Ad...mentioning
confidence: 99%